The contribution of dyadic empathy to the perception of marital quality - Todić, Ivan; Jelena; Trifunović, Biljana (Psihološka istraživanja, 2021)
The aim of this study was to examine the relationship between dyadic empathy and marital quality in formal and informal marital relationships in Serbia. Sample consisted of 738 participants (56.5% women), with different education, work and economic status. Average age of the sample was 30 years (SD = 9.66), ranging from 19 to 80 years. Participants live with their partners between a year and 52 years (M = 8.29, SD = 9.71). Interpersonal Reactivity Index for Couples (IRIC; Péloquin & Lafontaine, 2010) was applied in order to assess both cognitive and affective dimension of dyadic empathy, while marital quality was measured by the Dyadic Adjustment Scale (DAS; Spanier, 1976, 1989). The results of structural modeling indicate a positive contribution of affective empathy to the assessment of spousal agreement regarding issues that are important for everyday functioning, the assessment of general satisfaction with marriage, as well as the assessment of degree of closeness and quality of communication between partners; while cognitive empathy makes a positive contribution to the assessment of sposusal agreement regarding issues that are important for everyday functioning, the assessment of the agreement of the spouses concerning displays of affection, sexual relations, lack of love and denials of sex, as well as the assessment of the degree of closeness and quality of communication between partners.